PHRASEOLOGY AS A SUBSYSTEM OF THE LANGUAGE (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Phraseology means the branch of linguistics managing stable word mixes described by a specific transaction of significance. Notwithstanding contrasts of assessment, most creators concur upon certain focuses concerning the unmistakable elements of phraseological units, for example, Uprightness (or transaction) of importance implies that none of the saying parts is independently connected with any referents of genuine reality, and the significance of the entire unit can't be reasoned from the implications of its parts; Solidness (lexical and syntactic) implies that no lexical replacement is conceivable in an expression in correlation with free or variable word-mixes (with an exemption of certain situations when such replacements are made by the creator purposefully).